Optimalisasi Manajemen Produksi Layanan Digital Bank Syariah Studi Kasus Pada Mobile Banking BSI - Andi Yuniarti; Fuji Pratiwi; Indra Heri Rukmana; Muh Yasir; Dewi (Precise Journal of Economic, 2025)
Digital transformation in the Islamic banking sector has prompted Bank Syariah Indonesia (BSI) to develop the Byond BSI mobile banking service as an effort to improve efficiency and customer convenience. This study aims to analyze how digital service production management is implemented in the application and identify challenges and optimization efforts. The method used is descriptive qualitative based on literature review. The study results indicate that although Byond BSI has experienced significant growth, obstacles remain such as technical glitches, slow login processes, incomplete features, and the need for enhanced security. BSI has undertaken various improvement efforts, including system updates, digital education, and the development of Sharia-based features. Service optimization is carried out based on the five dimensions of SERVQUAL: tangibles, reliability, responsiveness, assurance, and empathy. If these dimensions are optimally implemented, service efficiency and convenience can be achieved, which ultimately impacts customer loyalty to BSI's digital services.